Prospective survey of veterinary practitioners’ primary assessment of equine colic: clinical features, diagnoses, and treatment of 120 cases of large colon impaction - Jennings, Kyra Megan (BioMed Central, 2014)
BACKGROUND: Large colon impactions are a common cause of colic in the horse. There are no scientific reports on the clinical presentation, diagnostic tests and treatments used in first opinion practice for large colon impaction cases. The aim of this study was to describe the presentation, diagnostic approach and treatment at the primary assessment of horses with large colon impactions. METHODS: Data were collected prospectively from veterinary practitioners on the primary assessment of equine colic cases over a 12 month period. Inclusion criteria were a diagnosis of primary large colon impaction and positive findings on rectal examination. Data recorded for each case included history, signalment, clinical and diagnostic findings, treatment on primary assessment and final case outcome. Case outcomes were categorised into three groups: simple medical (resolved with single treatment), complicated medical (resolved with multiple medical treatments) and critical (required surgery, were euthanased or died). Univariable analysis using one-way ANOVA and Tukey’s post-hoc test, Kruskal Wallis with Dunn’s post-hoc test and Chi squared analysis were used to compare between different outcome categories. RESULTS: 1032 colic cases were submitted by veterinary practitioners: 120 cases met the inclusion criteria for large colon impaction. Fifty three percent of cases were categorised as simple medical, 36.6% as complicated medical, and 9.2% as critical. Most cases (42.1%) occurred during the winter. Fifty nine percent of horses had had a recent change in management, 43% of horses were not ridden, and 12.5% had a recent / current musculoskeletal injury. Mean heart rate was 43bpm (range 26-88) and most cases showed mild signs of pain (67.5%) and reduced gut sounds (76%). Heart rate was significantly increased and gut sounds significantly decreased in critical compared to simple medical cases (p<0.05). Fifty different treatment combinations were used, with NSAIDs (93%) and oral fluids (71%) being administered most often. CONCLUSIONS: Large colon impactions typically presented with mild signs of colic; heart rate and gut sounds were the most useful parameters to distinguish between simple and critical cases at the primary assessment. The findings of seasonal incidence and associated management factors are consistent with other studies. Veterinary practitioners currently use a wide range of different treatment combinations for large colon impactions.